Multifunctionality of an arthropod predator’s body coloration - Liao, Hsien-Chun; Liao, Chen-Pan; Blamires, Sean J.; Tso, I-Min (Functional ecology, 2019)
Animal body colours can be shaped by many factors, including the need to attract mates, avoid predators and lure prey. In some contexts, these needs might compete. A number of studies have recently demonstrated that the silver, white, yellow or red bodies of spiders attract mates, lure prey or startle predators. Nevertheless, when spider bodies display different colours, little is known about the multifunctionality of the colours and whether they interact. The Australasian coin spider, Herrenia multipuncta, displays unconventional body coloration, with orange, black and grey regions across its body. We hypothesized that its coloration serves a multifunctional role, with the dorsal orange bands on its prosoma attracting prey and its orange ventrum deterring predators. We tested our hypothesis with field and laboratory experiments using dummies and real spiders, and modelling the visibility of the various colours to different predators and prey. Our field experiment showed significant prey attraction towards the orange‐grey dorsal pattern during the day and night, while our laboratory experiment showed that the lizard Japalura swinhonis stared at spiders and hesitated before attacking spiders when the orange abdominal region was uncovered. Our various visual models confirmed our experimental results by showing that the orange and grey body parts were always visible when contrasted against their natural backgrounds. Combined, our analyses provide evidence to conclude that the orange body colour of H. multipuncta is multifunctional, serving in both prey attraction and predator avoidance. A plain language summary is available for this article. Plain Language Summary